STATISTICAL APPRAISAL OF THE INTENSIFICATION OF FOREST USE - Lyudmila G. Moiseykina (Статистика и экономика)
Conclusions of the carried-out analysis of the statistical information characterizing an intensification of use of the woods, in particular, to the most frequent reason of deforestation are published in article - to deforestation. The analysis of existing indicators allowed to characterize forest exploitation process from the point of view of its extensiveness, however, for carrying out the full analysis of a state, reforestation and forest exploitation, in particular and deforestation, the system of the indicators characterizing these processes is necessary. The indicators characterizing intensity of forest exploitation are presented in article, from the point of view of deforestation.